Effects of propolis from Brazil and Bulgaria on fungicidal activity of macrophages against Paracoccidioides brasiliensis - Murad, J. M.; Calvi, S. A.; Soares, AMVC; Bankova, V; Sforcin, J. M. (Elsevier B.V., 2002)
Paracoccidioidomycosis is the most important systemic mycosis in Latin America. Its etiological agent, Paracoccidoides brasiliensis, affects individuals living in endemic areas through inhalation of airborne conidia or mycelial fragments. The disease may affect different organs and systems, with multiple clinical features, with cell-mediated immunity playing a significant role in host defence. Peritoneal macrophages from BALB/c mice were stimulated with Brazilian or Bulgarian propolis and subsequently challenged with P, brasiliensis. Data suggest an increase in the fungicidal activity of macrophages by propolis stimulation, independently from its geographic origin, (C) 2002 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: propolis; macrophage; yeast; Paracocridioides brasiliensis; Brazil; Bulgaria